Cobalt-free SrNbxFe1−xO3−δ (x = 0.05, 0.1 and 0.2) perovskite cathodes for intermediate temperature solid oxide fuel cells - Jiang, S.; Sunarso, J.; Zhou, W.; Shen, J.; Ran, R.; Shao, Zongping (Elsevier, 2015)
The development of high performance perovskite cathode for solid oxide fuel cells (SOFCs) relies upon the knowledge and understanding of the interplay between the metal oxide components, structure, redox properties and conductivity. In this work, we partially substituted Fe on SrFeO3−δ with Nb. In particular, 3 Nb-doped compositions were prepared, e.g. SrNb0.05Fe0.95O3−δ (SNF0.05), SrNb0.1Fe0.9O3−δ (SNF0.1) and SrNb0.2Fe0.8O3−δ (SNF0.2). Mössbauer spectroscopy revealed decreasing ratio of Fe4+ to Fe3+ at the higher Nb doping content which translates to the gradual decrease of the average Fe oxidation state from 3.403 (for SNF0.05) to 3.375 (for SNF0.1) and to 3.291 (for SNF0.2). Likewise, the oxygen desorption process and the thermal expansion coefficients decreased with increasing Nb content, therefore providing evidence on their correlation with the thermal reduction of Fe4+. The temperature-dependent oxygen nonstoichiometry displayed two different regimes separated by a transition temperature of 625 °C, below which SNF0.2 showed the highest nonstoichiometry and above which SNF0.05 provided the highest nonstoichiometry. The analogous shifting in trends was reproduced for oxygen reduction reaction (ORR) performance which signifies oxygen nonstoichiometry as the main variable affecting ORR performance.